2021
DOI: 10.1016/j.lanepe.2021.100159
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and reasons for use of Heated Tobacco Products (HTP) in Europe: an analysis of Eurobarometer data in 28 countries

Abstract: Background Heated Tobacco Products (HTP) are a relatively new class of tobacco products, with limited data on usage patterns. We assessed the prevalence and reasons for use among persons aged ≥15 years in 27 European Union member states and the United Kingdom· Methods The 2020 Eurobarometer (93·2) survey was analysed (n=28,300, aged ≥15). Multi-level regression analyses assessed socio-demographic differences in use while separate analyses investigated reasons for starti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 12 publications
4
51
0
1
Order By: Relevance
“…Our analyses were also limited by the fact that the Eurobarometer questionnaire did not distinguish between ECs and HTP and did not assess quitting attempts among people concurrently using cigarettes (dual users). Considering that many of the users of novel products also smoke cigarettes, 30 our findings may not be generalisable to all users of ECs and HTP. Separating HTP and ECs in survey questions and assessing in detail dual and polyusers are becoming increasingly essential considering their popularity.…”
Section: Discussionmentioning
confidence: 76%
“…Our analyses were also limited by the fact that the Eurobarometer questionnaire did not distinguish between ECs and HTP and did not assess quitting attempts among people concurrently using cigarettes (dual users). Considering that many of the users of novel products also smoke cigarettes, 30 our findings may not be generalisable to all users of ECs and HTP. Separating HTP and ECs in survey questions and assessing in detail dual and polyusers are becoming increasingly essential considering their popularity.…”
Section: Discussionmentioning
confidence: 76%
“…The need for such a fast turnaround and assessment of new 'variants of interest' is especially evident in light of the swift expansion of JUUL in the USA and the launch and proliferation of HTPs. [8][9][10][11] However, for its maximum potential to be reached, the issue of on March…”
Section: Increasing the Evidence Base On Tobacco Product Constituents...mentioning
confidence: 99%
“…30 Despite this notable drop in prevalence, the differential regulation of cigarettes and RYO tobacco compared with other smoked products (ie, cigarillos) and other products, such as e-cigarettes and HTPs, created inconsistencies concerning packaging, labelling, and flavouring and may have led to product displacement rather than a reduction in consumption, particularly among youth. 9 Cohort study research has indicated that the implementation of the TPD had altered smoking behaviour through changes in consumption patterns 37 38 but may also have led to product switching or displacement, which may partially explain some of the differences in prevalence for specific product categories. 39 40…”
Section: The Overall Impact Of the Tpdmentioning
confidence: 99%
See 2 more Smart Citations